(untitled) (Linguostylistic Studies, 2015)
The article is devoted to the issue of the interaction of the concepts BUSSINES and POLITICS in modern Ukrainian journalistic discourse. As a result of studying in journalistic texts the function of units representing these concepts, were established three types of semantic relations between these cognitive structures: identity, aggregate and connection. It was traced the relationship of identity may occur in static and dynamic aspects. There are regularities related to the fact that in the context with the relation of identity between lexical reprezentantatives of the concepts predicative relationship is established, based on the identification, and in the context with the semantics of aggregate and connection the main is figurative implementation of relations. Also the pragmatic component of the interaction of these concepts is traced, types of partial evaluations related to this process are defined. Statements that verbalize the relationship between theses concepts are interpreted as objectivators of social realities and ideas that reveal the content of concepts BUSSINES and POLITICS in modern Ukrainian linguistic worldview. Key words: concept sphere, evaluation, the subject of evaluation, types of partial evaluation, connotation, journalistic language. References